Effectiveness of educational intervention on perception regarding rabies among women self help group members in urban Mysore, Karnataka, India - Kulkarni, Praveen; D, Sunil Kumar; Siddalingappa, Hugara; M, Renuka (International Journal Of Community Medicine And Public Health, 2017)
Background: Each year 20,000 human deaths occur in India, which constitutes one third of the global burden. Majority of human rabies deaths occur due to inadequate knowledge regarding rabies and its prevention. Women self-help group (SHG) members can be trained and utilized to enhance rabies awareness in the community. Objective of the study is to assess the effectiveness of educational intervention on perception regarding rabies among women SHG members. Methods: This prospective interventional study was undertaken in an urban locality of Mysore for the period of three months. 110 women self-help group members willing to participate in the study were included. Their socio-demographic profile and baseline knowledge regarding rabies was collected in a pretested structured proforma. Rabies education was given through lecture and through a video film in local language. The same subjects were resurveyed at the end of one month to assess the change in their perception regarding rabies. Results: Among 110 subjects included in the pretest survey, 28 (25.5%) were aware of rabies but following educational intervention among 105 subjects participated in the post test survey, 85 (80.1%) had responded that they were aware of rabies. There was also significant improvement in the perception related to animals transmitting rabies, modes of transmission, first aid practices, post exposure prophylaxis following educational intervention. Overall, there was statistically significant difference in median knowledge scores before and after educational intervention. Conclusion: There was a significant improvement in perception regarding rabies among SHG members following simple educational intervention.